Penerapan Strategi Assessment Search Dalam Pembelajaran Pendidikan Agama Islam (PAI) di Sekolah Dasar Negeri - Priyantoro, Dian Eka; Trianingsih, Yuniada; Dwi Sartika, Desti; Rahman, M.Aldila (Universitas Islam Negeri (UIN) Jurai Siwo Lampung, 2022)
This journal has the aim of providing a discussion about learning Islamic religion in primary school which focuses on the application of strategy assessment tests in learning Islamic religion, teachers use imaginative and active strategies in an effort to create the potential of children. Therefore, it can be said that the learning methodology used by the teacher is half of the learning spirit because the learning strategy is the guide for learning in the classroom. In this journal, implement an assessment search strategy in Islamic religious education learning at one city Raman public elementary school which is part of a fun learning event. This learning strategy can be an adaptive strategy, this learning strategy in evaluating students in a fast time can also spur children's understanding well.